Conservation and iconographic analysis of early Buddhist wall paintings from southern Uzbekistan - Kageyama, Etsuko (Universitas Negeri Surabaya, 2024)
This paper delves into the conservation initiative undertaken for the wall paintings discovered at the Fayaztepa Buddhist site in southern Uzbekistan. It also presents findings from an iconographic study of the paintings. The Fayaztepa site, excavated by L. I. Al’baum in the 1970s, was found to be a Buddhist temple complex featuring a stupa and a monastery. The coins recovered during excavation indicated that the temple was operational during the Kushan dynasty (1st-3rd century AD). Some of the wall paintings discovered at the monastery have undergone treatment and are on display in the museum, while the rest are kept untreated at the Institute of Archaeology in Samarkand. Between 2016 and 2020, the author, in collaboration with the Institute of Archaeology, implemented a conservation project focused on the wall paintings from Fayaztepa. The conservation of four wall paintings was consequently completed and made available to the public. The murals representing stupas are particularly interesting and offer unique insights into the transmission of Buddhist art. The shape of umbrellas can be compared with small stone stupas found in Gandhara. The ornamentation of the umbrella with a net of strands of pearls and small bells traces its roots back to the balustrades of Bharhut, central India (2nd or 1st century BC). It is therefore likely that the decoration consisting of a net of pearls and bells was introduced from India to Central Asia through the Gandhara region.